2003
DOI: 10.2460/ajvr.2003.64.479
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study to investigate variation in results of repeated ELISA and culture of fecal samples for Mycobacterium avium subsp paratuberculosis in commercial dairy herds

Abstract: Analysis suggests that KELA results vary on a cow-level on the basis of lactation number and stage of lactation. High KELA values indicate heavy fecal shedding, but the KELA is not useful in identifying low and moderate shedders that can require up to 236 days to have a significant increase in KELA value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 9 publications
3
22
2
Order By: Relevance
“…The high and constant titres in the former pattern led us to hypothesise the existence of heavy-shedder cows, as already described for Escherichia coli [22,29] and Mycobacterium avium subsp. paratuberculosis (MAP) [32]. However, while heavy faecal shedding is recognised to have a high impact on E. coli or MAP transmission within a herd [22,32], the role of heavy milk shedders of Coxiella burnetii in bacterium transmission between animals and from animals to humans remains questionable [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high and constant titres in the former pattern led us to hypothesise the existence of heavy-shedder cows, as already described for Escherichia coli [22,29] and Mycobacterium avium subsp. paratuberculosis (MAP) [32]. However, while heavy faecal shedding is recognised to have a high impact on E. coli or MAP transmission within a herd [22,32], the role of heavy milk shedders of Coxiella burnetii in bacterium transmission between animals and from animals to humans remains questionable [4].…”
Section: Discussionmentioning
confidence: 99%
“…paratuberculosis (MAP) [32]. However, while heavy faecal shedding is recognised to have a high impact on E. coli or MAP transmission within a herd [22,32], the role of heavy milk shedders of Coxiella burnetii in bacterium transmission between animals and from animals to humans remains questionable [4].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these programs adopt necessary control measures in accordance with the degree of infection of each farm. Given the nature of the disease, however, diagnostic methods for Johne's disease do not always provide results with sufficient reliability to allow the estimation of farm prevalence [16,20]. Nevertheless, estimation of the degree of within-farm infection should assist animal health administrators to determine appropriate measures at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, detection of subclinically infected cattle is not easily achieved by current diagnostic methods owing to their strong dependence on the timing and proper use of diagnostic tests, as well as life stage or physiological condition of the cattle, including age or stress associated with pregnancy or calving [16,20]. As a result, infected farms in Japan are placed under regulatory monitoring with more frequent testing for a certain period determined by the respective prefecture [13,14].…”
mentioning
confidence: 99%
“…That is, cows that are consistently slow to conceive may have extended lactation periods relative to other cows in the herd and may be substantially older than other cows of the same parity. Previous studies have reported that cows in the second lactation and later have significantly higher ELISA values 24 and are 2-3 times more likely to have a positive ELISA result 17 compared with cows in the first lactation.…”
Section: Discussionmentioning
confidence: 99%